In‐band bootstrapping in database‐driven multi‐hop cognitive radio networks. (5th October 2016) - Jia, Juncheng; Wang, Dajin; He, Zhengqiu; Fan, Jianxi; Zhang, Shukui; Wang, Jin; Yan, Jianfeng
Summary: Database‐driven approach has emerged recently as an alternative or supplement for spectrum sensing for cognitive radio networks (CRNs). Within database‐driven CRNs, master devices obtain spectrum information by direct connection to a spectrum database, while slave devices can only access spectrum information indirectly via masters. The in‐band approach completely based on primary spectrum channels can be used, which eliminates the need for out‐of‐band connections and eases the adoption of the database‐driven spectrum sharing. In this paper, we study the in‐band bootstrapping process for database‐driven multi‐hop CRNs, where master/slave devices form a multi‐hop networks, and slaves need multi‐hop communications to obtain spectrum information from the master during bootstrapping. We start with the basic design of in‐band bootstrap protocol, whose performance is unsatisfactory of protocol overhead and bootstrap time. Then we propose 2 enhancements: first, we incorporates the recursive fractional spectrum information query scheme to reduce protocol overhead; then we propose the prefetch scheme to reduce the bootstrap time. According to the analysis and simulation results, our proposed protocols can greatly improve the performance: the recursive fractional spectrum information query enhancement reduces up to 40 % of the overhead, the prefetch enhancement reduces more than 20 % of the bootstrap time. Abstract : The in‐band approach completely based on primary spectrum channels can eliminate the need for out‐of‐band connections and eases the adoption of the database‐driven spectrum sharing. We study the in‐band bootstrapping process for database‐driven multi‐hop cognitive radio networks, where master/slave devices form a multi‐hop networks and slaves need multi‐hop communications to obtain spectrum information from the master. We propose the recursive fractional spectrum information query scheme to reduce protocol overhead, and the prefetch scheme to reduce the bootstrap time.